Usulan Peningkatan Kapasitas Produksi dengan Metode ConWIP di PT UTC Aerospace System Bandung Operation - Yudisthira Cahaya Putra Anugrah; Asep Anwar (Fakultas Teknik Universitas Tulang Bawang, 2026)
PT. UTC Aerospace Systems Bandung Operations faces challenges in meeting the production targets for Actuator Body Sub Assembly in Cell Shaft division, with a shortfall of 66 units per month and an impact on On Time Delivery. This research aims to identify and analyze capacity limiting factors and the root causes of production flow efficiency problems. The research methodology includes cycle time analysis to understand the processes and production flow, as well as a simulation of the current production system. This approach is used to investigate areas where WIP congestion occurs and how it hinders the smooth flow of production. Using a JaamSim based discrete simulation, this study analyzes the implementation of ConWIP to optimize production capacity in the Cell Shaft division. The analysis results show significant WIP congestion at operation station 1655, which hinders material flow and reduces production capacity. Through the JaamSim simulation, this study examines how the application of ConWIP can increase production capacity from 574 units to 576 units per month. Keywords: Bottleneck, Capacity, Constant Work In Process, Production Flow